Multivariate Pade Approximation for Solving Nonlinear Partial Differential Equations of Fractional Order - Turut, Veyis; Guzel, Nuran (HINDAWI LTD, 2013)
Two tecHniques were implemented, the Adomian decomposition method (ADM) and multivariate Pade approximation (MPA), for solving nonlinear partial differential equations of fractional order. The fractional derivatives are described in Caputo sense. First, the fractional differential equation has been solved and converted to power series by Adomian decomposition method (ADM), then power series solution of fractional differential equation was put into multivariate Pade series. Finally, numerical results were compared and presented in tables and figures.
Keywords: DECOMPOSITION METHOD; Mathematics